Periorbital Injection of Hyaluronic Acid Gel in Patients With Deep Superior Sulcus. Issue 1 (January 2020) - Sung, Youngje; Goldberg, Robert Alan; Lew, Helen
Abstract : Purpose: Hyaluronic acid gel (HAG) fillers provide a versatile and safe correction method for a sunken superior sulcus (SS) resulting from soft tissue volume loss occurring with aging, previous surgery, or enophthalmos related to trauma or phthisis bulbi. The purpose of this study was to report the long-term clinical outcomes of filler injection for soft-tissue augmentation in patients with a deep SS. Design: Retrospective, interventional case series Methods: The medical records of 27 patients (32 eyes) with deep superior sulci were reviewed. Twenty injections of hyaluronic acid fillers (Restylane; Q-med AB, Uppsala, Sweden) were performed in the retrobulbar (RB) area, and 15 injections were performed in the SS. Pre- and post-treatment photographs were taken. Main Outcomes Measures: Visual acuity for seeing eyes, intraocular pressure, exophthalmos measurement, marginal reflex distance 1, interpalpebral fissure, tarsal platform show, and SS hollowing depth grade Results: Enophthalmos corrections were 1.3 ± 0.8 mm ( P  < 0.001) and the SS hollowing grade decrease was 1.2 ± 0.9 ( P  < 0.01) after 1 month of RB injection. Enophthalmos corrections were 0.1 ± 0.4 mm ( P  = 0.317) and the SS sunkeness grade decrease was 1.7 ± 0.8 ( P  < 0.001) after 1 month of SS injection. The amount of filler to correct enophthalmos of 1 mm was 0.83 ± 0.53 mL using the RB injection. Using Kaplan-Meier survival analysis, the mean period of maintenance for deep SS correction was 9.1 months for RB injections and 8.5 months for SS injections. Conclusion: Retrobulbar (RB) hyaluronic acid gel (HAG) injections corrected enophthalmos and a deep SS, while SS injections corrected only a deep SS. These 2 techniques of RB and direct sulcus injection are safe and effective methods for the correction of a deep SS. Abstract : Supplemental Digital Content is available in the text